2013
DOI: 10.5194/acp-13-7007-2013
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric mercury over sea ice during the OASIS-2009 campaign

Abstract: Measurements of gaseous elemental mercury (GEM), reactive gaseous mercury (RGM) and particulate mercury (PHg) were collected on the Beaufort Sea ice near Barrow, Alaska, in March 2009 as part of the Ocean-Atmosphere-Sea Ice-Snowpack (OASIS) and OASIS-Canada International Polar Year programmes. These results represent the first atmospheric mercury speciation measurements collected on the sea ice. Concentrations of PHg averaged 393.5 pg m−3 (range 47.1–900.1 pg m−3) and RGM concentrations a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 65 publications
2
45
0
Order By: Relevance
“…Other aerosols such as sea salts and ice crystals are also common during the spring at Alert. Both these aerosols are effective scavengers of RGM and have been associated with elevated levels of PHg and Hg in the snow (Rutter and Schauer, 2007a;Douglas et al, 2008;Malcolm et al, 2010;Steffen et al, 2013). Coarse particle Na + , mostly sea salt derived, is elevated in February and at the beginning of March at Alert (Leaitch et al, 2014) but decreases in April.…”
Section: Gem (Ng Mmentioning
confidence: 99%
See 1 more Smart Citation
“…Other aerosols such as sea salts and ice crystals are also common during the spring at Alert. Both these aerosols are effective scavengers of RGM and have been associated with elevated levels of PHg and Hg in the snow (Rutter and Schauer, 2007a;Douglas et al, 2008;Malcolm et al, 2010;Steffen et al, 2013). Coarse particle Na + , mostly sea salt derived, is elevated in February and at the beginning of March at Alert (Leaitch et al, 2014) but decreases in April.…”
Section: Gem (Ng Mmentioning
confidence: 99%
“…Many studies have reported the decrease in GEM and a concurrent increase in oxidized mercury (PHg and RGM) and the connection of this chemistry to spring time ozone and halogen chemistry (Lindberg et al, 2001;Lindberg et al, 2002;Aspmo et al, 2005;Kirk et al, 2006;Cobbett et al, 2007;Simpson et al, 2007;Dastoor et al, 2008;Steffen et al, 2008;Steen et al, 2011). While atmospheric mercury speciation data in the Arctic air have been collected at several sites Kirk et al, 2006;Skov et al, 2006;Cobbett et al, 2007;Steen et al, 2011;Moore et al, 2012;Cole et al, 2013;Steffen et al, 2013;Brooks et al, 2006), few longterm (more than 5 years) mercury speciation measurements at temperate regions have been published and the Alert data set is the only such Arctic data set .…”
Section: Introductionmentioning
confidence: 99%
“…The reduction rate was found to be linearly correlated with UV intensity (Lalonde et al, 2002;Mann et al, 2015b), while Cl − showed an inhibiting effect on the photoreduction (Sect. 3.3) (Steffen et al, 2013). Oxidation and reemission of Hg 0 occurred simultaneously with the presence of oxidants (e.g., q OH, q Cl and q Br) formed through photolysis .…”
Section: Air-water Hg Exchangementioning
confidence: 99%
“…The snowpack plays an important role for the cycling of Hg, including for atmospheric deposition, photochemical oxidoreduction reactions, and associated phase changes between solid and gaseous Hg that can volatilize Hg to the atmosphere (Douglas et al, 2008;Faïn et al, 2013;Mann et al, 2014;Steffen et al, 2013). In particular, many temperate and arctic studies have shown that the snowpack can serve as sinks or sources of Hg 0 gas , whereby photochemical reduction of snow-bound Hg II …”
Section: Introductionmentioning
confidence: 99%